Health problems in travellers to Nepal visiting CIWEC clinic in Kathmandu — A GeoSentinel analysis. Issue 40 (March 2021) - Pandey, Prativa; Lee, Keun; Amatya, Bhawana; Angelo, Kristina M.; Shlim, David R.; Murphy, Holly
Abstract: Background: Nepal has always been a popular international travel destination. There is limited published data, however, on the spectrum of illnesses acquired by travellers to Nepal. Methods: GeoSentinel is a global data collection network of travel and tropical medicine providers that monitors travel-related morbidity. Records for ill travellers with at least one confirmed or probable diagnosis, were extracted from the GeoSentinel database for the CIWEC Clinic Kathmandu site from January 1, 2009 to December 31, 2017. Results: A total of 24, 271 records were included. The median age was 30 years (range: 0–91); 54% were female. The top 3 system-based diagnoses in travellers were: gastrointestinal (32%), pulmonary (16%), and dermatologic (9%). Altitude illness comprised 9% of all diagnoses. There were 278 vaccine-preventable diseases, most frequently influenza A (41%) and typhoid fever (19%; S . typhi 52 and S . paratyphi 62). Of 64 vector-borne illnesses, dengue was the most frequent (64%), followed by imported malaria (14%). There was a single traveller with Japanese encephalitis. Six deaths were reported. Conclusions: Travellers to Nepal face a wide spectrum of illnesses, particularly diarrhoea, respiratory disease, and altitude illness. Pre-travel consultations for travellers to Nepal should focus on prevention and treatment of diarrhoea and altitude illness, along with appropriate immunizations and travel advice.